A new method for simultaneous determination of 14 phenolic acids in agricultural soils by multiwavelength HPLC-PDA analysis. Issue 23 (18th May 2022) - Cheng, Jia; Zhou, Chunfu; Xie, Yue; Wang, Min; Zhou, Cheng; Li, XiaoShuang; Du, YaDong; Lu, Fan
Abstract : A method for multiple phenolic acids in soil based on HPLC-PDA multi-wavelength analysis was established. The method is high sensitivity, high accuracy and stable sample, and can be used for quantitative analysis of phenolic acids in soil. Abstract : There are phenolic acids with allelopathy in the rhizosphere soil of plants. At present, the identification and quantification of phenolic acids in different matrix mixtures is usually analysed by high performance liquid chromatography, but the detection of phenolic acids in soil has rarely been studied. As well as, previous studies have evaluated a limited number of target compounds. In this work, we proposed and verified a method for quantitative determination of 14 phenolic acids, including gallic acid, vanillic acid, p -hydroxybenzoic acid, protocatechuic acid, caffeic acid, syringic acid, p -coumaric acid, ferulic acid, chlorogenic acid, benzoic acid, salicylic acid, 2-methoxycinnamic acid, 3-methoxycinnamic acid, and cinnamic acid, which are widely present in rhizosphere soil of plants and have allelopathy. This method used multiwavelength HPLC-PDA analysis for simultaneous determination of these compounds. The detection wavelengths selected 254 nm, 280 nm, 300 nm, and 320 nm. Chromatographic separation of all compounds was achieved using a column of Shim-pack VP-ODS (250 mm × 4.6 mm, 5 μm), kept at 30 °C. Mobile phase A was acetonitrile, B was a 0.5% acetic acid aqueous solution, and the flow rate was 1.0 mL min −1 . Under the condition of gradient elution, the mobile phase A was acetonitrile, B was a 0.5% acetic acid aqueous solution, and the flow rate was kept constant at 1.0 mL min −1 . The 14 target phenolic acids were completely separated within 45 min. All the calibration curves showed good linearity, and the correlation coefficient was 0.9994–0.9999. With the detection limit varying from 0.003 mg L −1 to 0.239 mg L −1 . The recovery rates and the RSD of 14 phenolic acids were 80.54∼107.0% and 1.43–4.35%, respectively. This method has the characteristics of high sensitivity, high accuracy, and high recovery rate. This method is a novel technical means for the simultaneous analysis of compound phenolic acids in soil.